Silymarin: A Comprehensive Review - Kshirsagar, Ajay; Ingawale, Deepa; Ashok, Purnima; Vyawahare, Neeraj (Pharmacognosy Reviews)
Silymarin, a flavonolignan from the seeds of 'milk thistle' (Silybum marianum), has been widely used from ancient times because of its excellent hepatoprotective action. It is a mixture of mainly three flavonolignans, viz, silybin, silidianin and silychristine, with silybin being the most active. Silymarin has been used medicinally to treat liver disorders, including acute and chronic viral hepatitis, toxin/drug-induced hepatitis and cirrhosis and alcoholic liver diseases. It has also been reported to be effective in certain cancers. Its mechanism of action includes inhibition of hepatotoxin binding to receptor sites on the hepatocyte membrane; reduction of glutathione oxidation to enhance its level in the liver and intestine; antioxidant activity and stimulation of ribosomal RNA polymerase and subsequent protein synthesis, leading to enhanced hepatocyte regeneration. It is orally absorbed but has very poor bioavailability due to its poor water solubility. This review focuses on the mechanism of action, pharmacokinetics, pharmacodynamics, various pharmacological activities and toxicity of silymarin. The nontraditional use of silymarin may make a breakthrough as a new approach to protect other organs in addition to liver.
Keywords: Hepatoprotection; herbal drugs; milk thistle and silymarin